Evaluation and Improvement of Data Availability in WSNs Cluster Base Routing Protocol - Mujahid, Tabassum; Kartinah, Zen (Universiti Teknikal Malaysia (UTEM), 2017)
Protocols are one of the main aspect and essential feature of communication. In Wireless Sensor Networks (WSNs) different kinds of protocols and topologies are being used to support data transmission and data reliability issues. Hierarchical Cluster Base Routing Protocols (CBRP) is most famous due to their lower energy consumption and flexible network scalability characteristics. In CBR, the sensor nodes are divided into two kinds of responsibilities such are Cluster Heads (CHs) and Cluster Members (CMs). CH’s perform data aggregation and data fusion related tasks while CMs only sense the environmental parameters and forward to their respective CHs. However, the data is only stored on the Base Station (BS). Data availability is one of the main concerns in the CBRP, if any CHs or CMs or BS is damaged due to energy depletion or hardware failure, the sensed data will be loose. In this research paper, we have performed a few experiments to evaluate the data availability related issues in CBR due to interference, network and BS failure. Therefore, we suggest some improvement to ensure data availability in